Ecdysone Agonist: New Insecticides with Novel Mode of Action - Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2002)
Development of insect resistance to insecticide has been the major driving force for the development of new insecticides. Awareness and demand from public for more environmentally friendly insecticides have contributed in shifting the trend from using broad spectrum to selective insecticides. As a result, scientists have looked for new target sites beyond the nervous system. Insect growth regulators (IGRs) are more selective insecticides than conventional insecticides, and ecdysone agonists are the newest IGRs being commercialized, e.g. tebufenozide, methoxyfenozide, and halofenozide. Ecdysone agonists bind to the ecdysteroid receptors, and they act similarly to the molting hormone 20-hydroxyecdysone. The binding provides larvae or nymphs with a signal to enter a premature and lethal molting cycle. In addition, the ecdysone agonists cause a reduction in the number of eggs laid by female insects. The ecdysone agonists are being developed as selective biorational insecticides. Tebufenozide and methoxyfenozide are used to control lepidopteran insect pests, whereas halofenozide is being used to control coleopteran insect pests. Their selectivity is due to differences in the binding affinity between these compounds to the receptors in insects from different orders. The selectivity of these compounds makes them candidates to be used in combinations with other control strategies to develop integrated pest management programs in agricultural ecosystems.